Effects of sleep deprivation on heart rate variability: a systematic review and meta-analysis - Zhang, Suling; Niu, Xiaodan; Ma, Jinke; Wei, Xin; Zhang, Jun; Du, Weiping (Frontiers in Neurology, 2025)
BackgroundSleep deprivation is prevalent in high-pressure environments and among shift workers, and may contribute to autonomic nervous system (ANS) dysregulation, contributing to cardiovascular diseases, mood disorders, and cognitive impairment. Heart rate variability (HRV), an important indicator of ANS function, reflects fluctuations in sympathetic and parasympathetic activity and is commonly used to assess the autonomic effects of sleep deprivation. However, existing studies exhibit considerable heterogeneity due to inconsistencies in HRV measurement methods, variations in deprivation duration, and inadequate control of confounding factors.ObjectiveThis study aimed to comprehensively evaluate the impact of sleep deprivation on HRV through a systematic review and meta-analysis of randomized controlled trials (RCTs), to elucidate the potential mechanisms underlying sleep deprivation-induced cardiac autonomic dysfunction, and to provide insights for optimizing sleep-related interventions and preventing cardiovascular disease.MethodsA systematic search was conducted in PubMed, Embase, CNKI, Wanfang, and VIP databases for RCTs investigating the effects of sleep deprivation on HRV, covering the period from January 2010 to May 2024. The Cochrane Risk of Bias tool was used for methodological quality assessment. Meta-analyses were performed using Review Manager 5.4 and Stata 17.0 software.ResultsA total of 11 eligible studies involving 549 participants were included. The meta-analysis revealed that: (1) In the time domain, sleep deprivation was associated with a non-significant reduction in SDNN (p > 0.05), while RMSSD showed a significant decrease (p < 0.05). (2) In the frequency domain, both LF and LF/HF significantly increased after sleep deprivation (p < 0.05), whereas HF showed a decreasing trend that did not reach statistical significance (p > 0.05).ConclusionThis meta-analysis indicates that sleep deprivation may impair cardiac autonomic function, as evidenced by decreased RMSSD and increased LF and LF/HF, suggesting sympathetic predominance and vagal suppression. However, changes in other HRV indices such as SDNN and HF were not statistically significant. These findings imply a potential disruption of the dynamic balance between sympathetic and parasympathetic activity following sleep deprivation. Future research should adopt standardized HRV measurement protocols to validate these findings and further explore the underlying physiological mechanisms. This study provides important evidence for understanding the dynamic changes in autonomic function associated with sleep deprivation.Systematic review registrationhttps://inplasy.com/projects/, identifier INPLASY202560023.